Exploring the Dimensions of E-learning Maturity Model - Iskander, George Maher (International Journal of Emerging Technologies in Learning (iJET), 2012)
Despite the highlighting on e-learning, it was obvious that models for successful deployment have not yet been recognized. Even with the huge quantities of money being spent, it is not clear that any enhancement in student learning outcomes has been recognized. To address this issue, this qualitative research aimed to explore and understand dimensions of E-learning Maturity Model (ELMM). An inductive approach, using qualitative methods, was used in this research. Fifty interviewees suggested five dimensions: Students’ Attitudes, University attitudes from studentsâ?? perspectives, E-learning features, E-learning implementation and Effects of E-learning on students. Students from different majors and levels participated in this study. Findings of this study show that, there are significant five factors which formulate ELMM. Moreover, the study demonstrates that e-learning features have significant effects on student. It also highlights the relevance of using qualitative research in exploring maturity concept in e- learning.